2017
DOI: 10.1021/acs.jchemed.7b00012
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Edible Oils by Principal Component Analysis of 1H NMR Spectra

Abstract: Principal component analysis (PCA) is a statistical method widely used in chemometric studies to analyze large, correlated sets of data. An undergraduate laboratory experiment involving PCA of 1H NMR spectral data is described. Students collect NMR spectra of an unknown oil sample, are provided with spectra of six oil standards (canola, corn, olive, peanut, sesame, and sunflower oil), and are asked to identify the unknown oil using score plots based on the PCA results. This laboratory experiment gives students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 37 publications
0
30
1
Order By: Relevance
“…Evidence-Based Complementary and Alternative Medicine that demonstrated strong antimicrobial activity. Anderson et al [49] identified several compounds of 6 oil samples using the combination of 1 H-NMR and the principle component analysis (PCA). In another study, NMR analysis was used to discriminate several oils including olive, hazelnut, and sunflower [50].…”
Section: Resultsmentioning
confidence: 99%
“…Evidence-Based Complementary and Alternative Medicine that demonstrated strong antimicrobial activity. Anderson et al [49] identified several compounds of 6 oil samples using the combination of 1 H-NMR and the principle component analysis (PCA). In another study, NMR analysis was used to discriminate several oils including olive, hazelnut, and sunflower [50].…”
Section: Resultsmentioning
confidence: 99%
“…The original relaxation fingerprint data were normalized by dividing the intensity of the signal acquired by using the single pulse excitation experiment with the same experimental conditions. Edible oil analysis methods have relied heavily on PCA owing to its high reliability and versatility [ 35 , 36 , 37 ]. In this work, PCA was applied to verify the capability of the relaxation fingerprints approach in edible vegetable oils discrimination.…”
Section: Methodsmentioning
confidence: 99%
“…1 Readers may examine Figure S7 (student data with faculty-corrected referencing) of Anderson et al's paper. 2 Second, to clarify the efficacy of our published technique, 2 we include here ( Figure 1) additional examples of studentacquired and student-analyzed data using the reported untargeted methodology, which achieved very good classification.…”
mentioning
confidence: 99%
“…In our report, 2 we included a discussion of some of the features that emerged from the unbiased PCA analysis, and not surprisingly, these features are very similar to the features that were used by Yeh 1 and reported by Vigli et al 3 We wish to reiterate that our work focused not on optimizing clustering, which has been ably demonstrated in the research literature, but on an efficient and rugged hands-on experiment that provides students with an authentic, entrylevel learning experience in multivariate analysis that could be completed in one laboratory period, has assessable learning goals, and accurately represents the initial steps in unbiased variable reduction and data clustering. 2 In order to model for students the general approach taken in research, we purposefully chose an untargeted analysis. The subsequent grouping, filtering, and scaling within MetaboAnalyst 4 lead to excellent oil classification, and the efficient workflow is important to enabling students to conduct the work within the time constraints of the laboratory period.…”
mentioning
confidence: 99%
See 1 more Smart Citation